2007
DOI: 10.1152/jn.01136.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Anticipatory Postural Adjustments Prior to Stepping

Abstract: .Step initiation involves anticipatory postural adjustments (APAs) that propel the body mass forward and laterally before the first step. This study used a startle-like acoustic stimulus (SAS) and transcranial magnetic stimulation (TMS) to examine the preparation of APAs before forward stepping. After an instructed delay period, subjects initiated forward steps in reaction to a visual "go" cue. TMS or SAS was delivered before (Ϫ1,400 or Ϫ100 ms), on (0 ms), or after (ϩ100 ms for TMS, ϩ200 ms for SAS) the imper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
146
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(162 citation statements)
references
References 49 publications
14
146
2
Order By: Relevance
“…Thus they suggested that sufficient details of a prepared movement may have been stored subcortically, possibly in the brain stem and spinal centers that were accessible to the startle volley, so that in some cases, it could be triggered early. Several later experiments replicated and extended these findings (Carlsen et al 2003b(Carlsen et al , 2004b(Carlsen et al , 2007Castellote et al 2007;Cressman et al 2006;MacKinnon et al 2007;Siegmund et al 2001). For example, it was found that response kinematics and EMG patterns are unchanged between control and startle elicited movements (Carlsen et al 2004b) and that the paradigm can be extended to different effectors and movement types such as saccades (Castellote et al 2007) and anticipatory postural adjustments (MacKinnon et al 2007).…”
Section: Introductionmentioning
confidence: 78%
“…Thus they suggested that sufficient details of a prepared movement may have been stored subcortically, possibly in the brain stem and spinal centers that were accessible to the startle volley, so that in some cases, it could be triggered early. Several later experiments replicated and extended these findings (Carlsen et al 2003b(Carlsen et al , 2004b(Carlsen et al , 2007Castellote et al 2007;Cressman et al 2006;MacKinnon et al 2007;Siegmund et al 2001). For example, it was found that response kinematics and EMG patterns are unchanged between control and startle elicited movements (Carlsen et al 2004b) and that the paradigm can be extended to different effectors and movement types such as saccades (Castellote et al 2007) and anticipatory postural adjustments (MacKinnon et al 2007).…”
Section: Introductionmentioning
confidence: 78%
“…It is known that there is a significant cortical involvement in predictive postural behavior. Mackinnon et al (2007) demonstrated a facilitation of the muscles involved in APAs, whereas anticipatory adjustments of arm muscles were absent in patients with damage to their motor cortex (Viallet et al 1992). Moreover, animal studies have suggested that the cortex contributes to motor planning of reaching during stance (Martin and Ghez 1985;Perfiliev 2005;Perfiliev 1998;Vicario et al 1983) and the feedforward adjustments accompanying the reach (Yakovenko and Drew 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing a startling stimulus have consistently shown that the movement triggered during startle trials is similar in movement kinematics and EMG configurations to that of control trials. This has been shown for such diverse tasks as upper arm and wrist movements (e.g., Carlsen et al 2004b, Maslovat et al 2008Valls-Solé et al 1999), stepping and gait initiation (MacKinnon et al 2007;Queralt et al 2010;Reynolds and Day 2007), head rotations (Oude Nijhuis et al 2007;Siegmund et al 2001), sit to stand (Queralt et al 2008), and rise to tiptoes (Valls-Solé et al 1999). However, most of these experiments have used a spatially defined movement whereby participants move to a predetermined target as fast as possible.…”
mentioning
confidence: 83%